Promising digital solutions for medical management of patients with oncological diseases - A. A. Zavyalov; D. A. Andreev (Здоровье мегаполиса)
Introduction. Malignant neoplasms remain a serious challenge for society, occupying the leading places next to cardiovascular pathology in the structure of causes of death in the vast majority of developed countries of the world. The wide popularization of innovative digital technologies in a professional clinical environment that does not have training in the relevant branches of physical and mathematical specialties is the key to the development and implementation of automated quality assessments. This fully meets the goals and objectives of the federal project “Fight against oncological diseases”, aimed at a drastically reduction in cancer mortality by 2024 among the population of the Russia. Purpose. Generalization of innovative individualized technological solutions to provide patients with high quality cancer care.Methods and materials. The scientific study was performed based on the results of a search using the PubMed / Medline database and the Google system. The search period covered about 6 years.Results. The article reflects examples of new digital solutions for medical management and the registration of multi-parametric indicators of oncological care at patient-oriented level. Among the actual solutions of mobile /remote e-health for cancer patients it is necessary to highlight: 1) portable (individual) medical gadgets; 2) “smart” piezoelectric necklaces; 3) implantable and internal sensors; 4) devices for performing blood tests at home in patients receiving chemotherapy; 5) mobile antitumor devices; 6) devices that implement neurotechnologies for pain relief; 7) integrated remote monitoring system.Findings. In the context of the spread of digital innovations a new environment is emerging, in which patient autonomy, collaborative medical decision making based on patient preferences, and ensuring wide access to the latest information technologies and resources are gradually becoming routine standards for providing oncological care.